AKUNTABILITAS PERSEMBAHAN DI MASA PANDEMI COVID-19 PADA GEREJA X DI MAKASSAR - Bertha Beloan; Cecilia Poddala; Maiercherinra Daud; Machmud Djunaidy (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2022)
This research was conducted at a religious organization,namely Church X in Makassar, which aims to determine the practiceof accountability for offerings during the Covid19 pandemic atChurch X in Makassar. By using qualitative descriptive researchmethods by conducting in-depth interviews with informants. Theresults showed that the practice of offering accountability to ChurchX is a form of accountability to God in the form of honesty, and full ofjoy in serving, so the accountability that is carried out is manifestedin the form of spiritual accountability to God who has given the task.